Petrography, geochemistry and geochronology of mafic to felsic dikes of the Água Azul do Norte region, southeast of Pará, Carajás Province - Rodrigues, Paulo Roberto Soares; Lamarão, Claudio Nery; Costa, Hévila de Nazaré Silva da; Oliveira, Davis Carvalho de; Galarza, Marco Antônio; Sotero, Aldemir de Melo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
In the Água Azul do Norte region, southeast of Pará, mafic to felsic dikes, with dominant NW-SE direction and thicknesses of about 30 meters, outcrop in razed areas as discontinuous ridges sectioning anorogenic granites and Archean country rocks. Metaluminous to weakly peraluminous diabases, andesites, rhyolites and alkali-feldspar rhyolite with tholeiitic affinity were individualized. The diabase has the lowest content of SiO2 and TiO2 and the highest content of FeOt, MgO and CaO. The andesites have intermediate values when compared to diabases and rhyolites. The dikes of rhyolite and alkali-feldspar rhyolite are more enriched in SiO2 and exhibit negative correlation of FeOt, Al2O3, MgO, CaO and positive correlation of K2O in relation to silica. The dikes of Água Azul do Norte show great similarity to those of other regions of the Rio Maria Domain, implying the same origin to the dykes of that region. However, the evolution of the dikes of Água Azul do Norte does not point to the existence of a continuous magmatic series. The geochronological data confirm the synchronism of felsic dykes with anorogenic granites of approximately 1.88 Ga of the Rio Maria Domain.
Keywords: Carajás Province; Água Azul do Norte; Dikes; Petrography; Geochemistry